Pengaruh Beban Pokok Penjualan terhadap Laba Bersih pada PT Indomarco Prismatama (Indomaret) - Angeline Suhandra Dharma; Elizabeth Tiur Manurung (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of Cost of Goods Sold (COGS) on Net Profit at PT Indomarco Prismatama (Indomaret) during the 2020–2024 period. As a key of component in the income statement, COGS has directly relationship with the company’s profitability. This research uses a quantitative method with a simple linear regression analysis approach. The data analyzed consist of secondary data in the form of the company's quarterly financial statements. The results reveal a significant positive correlation between COGS and Net Profit, with a coefficient of determination (R Square) of 0.816. This indicates that 81.6% of the variation in net profit can be explained by changes in COGS. Furthermore, a regression coefficient of 0.791 and a significant p-value below 0.05 indicate that COGS has a significant influence on net profit. These findings confirm that efficient COGS management is a key factor in enhacing company’s profitability. This research  is expected to contribute to corporate management in strategic decision-making and serve as a reference for further studies in the fields of finance and accounting.